The effect of age on the early stage of face perception in depressed patients: An ERP study - Shi, Hui; Sun, Gang; Zhao, Lun (Frontiers in Psychiatry, 2022)
The aim of the present study was to investigate the age effect on the face perceptual processing, especially the perceptual computation in the early stage of processing faces, in MDD patients, by analyzing the N170 of ERP components in response to faces and objects presented in upright and inverted conditions. For normal controls, although the N170 amplitude, overall, did not differ between young and middle-aged participants, the size of N170 inversion effect was larger for young than for middle-aged controls, but the N170 face effect was not influenced by age. For young participants, MDD patients showed N170 amplitude similar to controls and neither the N170 face effect nor the N170 inversion effect were influenced by depression. For middle-aged participants, MDD patients revealed larger N170 than did controls, both the size of N170 inversion effect and the N170 face effect were larger for MDD patients than controls. These data indicate that at least at the early stage of face perception, there is an altered face perception in middle-aged but not in young MDD patients and provide new evidence for clinical assessment of cognitive function in MDD patients.